Interest rate fluctuations and the UK financial services industry - Artikis, Panayiotis G.; Kalotychou, Elena; Staikouras, Sotiris K. (My University, 2007)
The article explores the relationship between short-term interest rates and the equity returns of the UK financial services industry. Based on the arbitrage pricing theory, the present study seeks to answer the sensitivity and pricing questions. The former is tested with a linear two-index model attempting to identify any interest rate risk exposure of these stock returns. The latter, however, is examined using a nonlinear multivariate analysis based on the Seemingly Unrelated Regression Equations (SURE) model by imposing cross- and within-equation constraints on the estimated parameters. The econometric analysis unveils a significant negative interest rate effect and the existence of a risk premium incorporated in the expected returns of portfolios consisting of these stocks.